2014
DOI: 10.1039/c4tc00992d
|View full text |Cite
|
Sign up to set email alerts
|

Electroless methods for molecular doping of gold thin films

Abstract: We developed electroless-based methods for entrapping molecules within gold thin films, molecule@Au. These doping procedures extend the potential library electroless formed films much beyond its classical application of pure metals. A detailed study shows that adsorption on gold films and entrapment within it provide distinctly different modified thin films. Significantly, molecules that cannot be adsorbed, do form an organic-metallic hybrid by the developed entrapment processes. We also report on the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…They also developed electroless based deposition to grow hybrid films of metal aggregates entrapping molecular guests. [494] Such structure can lead to rather homogeneous hybrid films with very interesting properties such as enhanced Raman response. They also interestingly showed that they were able to recover part of the emission of the Rhodamine.…”
Section: Encapsulation Of Dyes In Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also developed electroless based deposition to grow hybrid films of metal aggregates entrapping molecular guests. [494] Such structure can lead to rather homogeneous hybrid films with very interesting properties such as enhanced Raman response. They also interestingly showed that they were able to recover part of the emission of the Rhodamine.…”
Section: Encapsulation Of Dyes In Metalsmentioning
confidence: 99%
“…They also interestingly showed that they were able to recover part of the emission of the Rhodamine. [494] Such optical systems are Figure 43. Suggested structure of molecularly doped metals (left).…”
Section: Encapsulation Of Dyes In Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reflection peaks at 2θ value of 38.62°, 44.8°, 65°, 80°, and 82.2° correspond to (111), (200), (220), (311), and (222) reflection plane, indicating characteristics of face‐centered cubic Au, while Gd‐CoB does not show any apparent diffraction peak. [ 26 ] The XRD results further confirm the amorphous nature of the Gd‐CoB film. The thickness of nanosheets was further characterized by the atomic force microscopy technique (AFM).…”
Section: Resultsmentioning
confidence: 63%
“…Utilization of metal nanoparticles (NPs) in the enhancement of fluorescence emission was widely described in literature; however, the main emphasis was often put to the organic or inorganic modified compounds interacting with metal nanoparticles [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18]. The hybrid systems are often devoted to imaging with assistance of gold nanoparticles [19], cancer treatments [20], where NPs introduced to the cancer tissue are responsible for thermolysis of tumor by selective laser irradiation [21,22], sensing or photovoltaics [7,23].…”
Section: Introductionmentioning
confidence: 99%